Role of Mitochondria in Ferroptosis - Gao, Minghui; Yi, Junmei; Zhu, Jiajun; Minikes, Alexander M; Monian, Prashant; Thompson, Craig B; Jiang, Xuejun (Molecular cell, 2019)
Ferroptosis is a regulated necrosis process driven by iron-dependent lipid peroxidation. Although ferroptosis and cellular metabolism interplay with one another, whether mitochondria are involved in ferroptosis is under debate. Here, we demonstrate that mitochondria play a crucial role in cysteine-deprivation-induced ferroptosis but not in that induced by inhibiting glutathione peroxidase-4 (GPX4), the most downstream component of the ferroptosis pathway. Mechanistically, cysteine deprivation leads to mitochondrial membrane potential hyperpolarization and lipid peroxide accumulation. Inhibition of mitochondrial TCA cycle or electron transfer chain (ETC) mitigated mitochondrial membrane potential hyperpolarization, lipid peroxide accumulation, and ferroptosis. Blockage of glutaminolysis had the same inhibitory effect, which was counteracted by supplying downstream TCA cycle intermediates. Importantly, loss of function of fumarate hydratase, a tumor suppressor and TCA cycle component, confers resistance to cysteine-deprivation-induced ferroptosis. Collectively, this work demonstrates the crucial role of mitochondria in cysteine-deprivation-induced ferroptosis and implicates ferroptosis in tumor suppression.